Pengaruh Inflasi dan Tingkat Suku Bunga Terhadap Pertumbuhan Ekonomi di Indonesia - Andy Hakim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Inflation is an increase in the prices of goods and services on an ongoing basis. The research objective was to determine the effect of inflation and interest rates on economic growth in Indonesia. The research data comes from time series data, namely from 2003 - 2022. Where the data is obtained from various sources, such as www.bi.go.id, www.bps.go.id and www.kemenkeu.go.id. In this study, researchers conducted research with quantitative methods. Data analysis is statistical in nature with the aim of testing the research hypothesis that has been set previously. In this study used multiple linear regression analysis method. Multiple linear regression using SPSS 22 software. The results of this study are that inflation has a significant effect on economic growth in Indonesia, obtained tcount = 0.895 < ttable = 1.734. Interest rates have an effect on economic growth in Indonesia, where tcount = 0.056 < ttable = 1.734. While inflation and interest rates together affect economic growth in Indonesia, the value of Fcount = 4,618 is greater than the value of Ftable = 2.57.